2018
DOI: 10.1093/ons/opy034
|View full text |Cite
|
Sign up to set email alerts
|

Folate Receptor Near-Infrared Optical Imaging Provides Sensitive and Specific Intraoperative Visualization of Nonfunctional Pituitary Adenomas

Abstract: Preoperative injection of folate-tagged NIR dye provides strong signal and visualization of NF pituitary adenomas. It is 100% sensitive and specific for detecting margin neoplasm and can predict postoperative MRI findings. Our results suggest that NIR fluorescence may be superior to white-light visualization alone and may improve resection rates in NF pituitary adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Although this study used fluorescein as the fluorescent dye for CLE, other fluorophores have the potential to aid in the visualization of pituitary adenomas. Other studies have assessed the efficacy of two near-infrared (700–850-nm) fluorophores in pituitary adenoma resections: indocyanine green (ICG) and OTL38 (On Target Laboratories, West Lafayette, IN, USA) [ 26 , 27 , 28 ]. ICG, a dye frequently used in neurosurgery, can be applied in a technique known as second-window ICG, which uses the enhanced vascular permeability of pituitary adenomas to allow for intraoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study used fluorescein as the fluorescent dye for CLE, other fluorophores have the potential to aid in the visualization of pituitary adenomas. Other studies have assessed the efficacy of two near-infrared (700–850-nm) fluorophores in pituitary adenoma resections: indocyanine green (ICG) and OTL38 (On Target Laboratories, West Lafayette, IN, USA) [ 26 , 27 , 28 ]. ICG, a dye frequently used in neurosurgery, can be applied in a technique known as second-window ICG, which uses the enhanced vascular permeability of pituitary adenomas to allow for intraoperative imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In order to avoid this, the surgeon should attempt to visualize areas of suspected NIR fluorescence from a set distance. With the VisionSense Iridium endoscope in transsphenoidal surgeries for pituitary adenomas using a related NIR dye, we demonstrated that having the endoscope at a distance that maintains the distance between the two medial opticocarotid recesses to be <50% of the field of view is ideal for minimizing false-positive NIR signals ( Figures 8E – H ) ( 60 , 61 ). Endoscopes that offer more precise distance measurements could further help the neurosurgeon to acquire more accurate NIR signals.…”
Section: Practical Experiencementioning
confidence: 95%
“…In fact, multiple such conjugates are currently being investigated in preclinical and clinical trials for different intracranial tumors. For instance, folate-receptor overexpression on nonfunctional pituitary adenomas and meningiomas may provide targets for sensitive and specific detection of these tumors in real-time ( 54 , 60 62 ). An alternative is to use imaging apparatus with higher resolution for fluorescence, which may better distinguish true areas of fluorescence from areas of false-positive fluorescence.…”
Section: Future Researchmentioning
confidence: 99%
“…7,8,21 While FRa-targeted tomographic imaging with SPECT is capable of estimating FRa expression levels preoperatively, the cost-to-benefit analysis of preoperatively scanning all patients is unclear. 11 Instead, we have data 3 suggesting that initial NIR SBR of > 2.5 upon tumor exposure may predict FRa overexpression with near-100% probability; thus, a reasonable and affordable approach to using OTL38 clinically might be to administer it to all patients with nonfunctioning adenomas and determine intraoperatively whether each adenoma overexpresses FRa to decide if OTL38 fluorescence would be reliable for that surgery. If the initial SBR prior to resection is < 2.5, resection should proceed using conventional techniques without NIR imaging.…”
Section: Folate-receptor-targeted Imaging Is Highly Sensitive and Specific For Neoplasmmentioning
confidence: 98%